Apie A. Tatarės „Pamokslų išminties ir teisybės“ (1851 m.) kalbą - Zinkevičius, Zigmas (Baltistica, 1981)
Concerning the language of А. Тatarė’s „Пamokslai išminties ir teisybės" (1851)Even three variants of the language of Lithuanian writing were taking shape in the 16th–17th centuries: one in the Duchy of Prussia (based on the local West Aukštaičiai dialects) and two in the Grand Dukedom of Lithuania (based on the dialects of the middle Lithuanian plains, the district of Kėdainiai, and the town of Vilnius and its environs). Owing to the polonization of the Lithuanian gentry, the last two variants of Lithuanian writing disappeared in the 18th century. With the onset of the movement for national independence, in the second half of the 19th century Lithuanian proper followed the old tradition of writing as used by Lithuanians in East Prussia. The writing was adapted to suit the needs of Lithuania and somewhat modified to bring it closer to the local dialects of the southern part of West Aukštaičiai (the dialect of „Suvalkai"). Thus came into being Modern Lithuanian. To reveal the process of its formation, one must ascertain who was the first in Lithuanian proper to write in the Southern dialect of West Aukštaičiai. The author of the paper considers A. Tatarė (1805–1889) to be such a man. In the paper the author gives a linguistic analysis of Tatarė's major work „Pamokslai išminties ir teisybės" and points out the difficulties the scholar met trying to create written Lithuanian on the basis of the southern dialects of West Aukštaičiai.
Keywords: Tatarė; language of lithuanian writings; Western aukštaičiai dialect in writing